Simulation of a process control system for cyber-security analysis - Chen, RuoZhu (2018)
This report discusses a 3d real-time simulation model of a Smart Manufacturing system using Webots, a robot simulator. To begin with, the assembling manufacturing system is built using simulator Webots. In this model, a gripper robot and a group of unmanned workstations are deployed on an open floor platform. Workpieces need to be processed through different workstations according to the specific schedule order. The whole process control is realized by a supervisory control in discrete event systems. When the controller is designed, an automata debugger tool, developed by Cyber-Physical Intelligent System Research Group @ Nanyang Technological University, School of EEE, will be used to connect the supervisory controller in discrete event systems with the 3D simulation. As a result, the simulation can be controlled by changing the event sequences in the debugger tool and translates the discrete event system to real-time simulation. The simulation model in this study is expected to be useful for cyber-security analysis of the smart manufacturing system and for decision-making on the implementation of new strategies on the manufacturing system.